2019
DOI: 10.3390/s19143113
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Ambient Intelligence in Real Life: Dealing with Noisy Patterns to Help Older People

Abstract: This paper aims to contribute to the field of ambient intelligence from the perspective of real environments, where noise levels in datasets are significant, by showing how machine learning techniques can contribute to the knowledge creation, by promoting software sensors. The created knowledge can be actionable to develop features helping to deal with problems related to minimally labelled datasets. A case study is presented and analysed, looking to infer high-level rules, which can help to anticipate abnorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…A cloud based IoMT platform as a multi-layered architecture was proposed to sense and collect patients' information of their vitals and surrounding environment for AAL [26]. With the objective of "aging well at home," an IoT-based smart home automation-enabled health monitoring and the assistive system was proposed to assist in caring for sick and elderly persons around the clock [3]. A non-invasive ambient intelligence for older…”
Section: Ambient Assisted Living For Elderly Activities Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…A cloud based IoMT platform as a multi-layered architecture was proposed to sense and collect patients' information of their vitals and surrounding environment for AAL [26]. With the objective of "aging well at home," an IoT-based smart home automation-enabled health monitoring and the assistive system was proposed to assist in caring for sick and elderly persons around the clock [3]. A non-invasive ambient intelligence for older…”
Section: Ambient Assisted Living For Elderly Activities Monitoringmentioning
confidence: 99%
“…In this section, the proposed technique for elderly activity recognition for AAL is evaluated in experiments over the recorded AAL dataset and MHealth benchmark dataset [5]. Leveraging the benefits of smart sensors and deep learning techniques, experiments were performed with GRU and BiGRU deep learning techniques and compared with SVM, Naive Bayes,Decision Trees and with machine learning techniques proposed by other researchers [1,3,6,23]. This experimentation aims to produce an efficient model capable of effectively detecting the daily activities of elderly people to continuously monitor their wellbeing.…”
Section: Experimentationmentioning
confidence: 99%
“…When data are related to people, such as devices which are linked to apps by bluetooth, the apps are mostly designed to present the data to users and upload summaries to the cloud manufacturer [35]. However, data integration (especially when related to people) has limitations related to privacy and misuse [36,37]. Cyber security is vulnerable, as wearable device manufacturers have reduced their safety protocols and safety stack layers to enable cheap products, as they have been understood as only serving the end user in a local context.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the main objectives of the scientific community is to monitor and accurately identify the activity patterns of the elderly. Different studies have shown that the activity patterns of the elderly are a valid parameter to predict their quality of life [6]. There are approaches in this area to propose new algorithms, techniques, or systems to improve activity monitoring such as [7], focused on collecting different types of home surveillance technologies for monitoring behaviour of older people, or [8], where an architecture is developed that exploits the benefits of the Internet of Things (IoT) to capture location and other data to detect patterns of behaviour in older people in a nonintrusive way, or [7], where an IoT detection infrastructure for the city is presented that through REST and Linked Open Data application programming interfaces (APIs) collect and present data related to older people.…”
Section: Introductionmentioning
confidence: 99%